Impact Of Strain Rate On Mechanical Properties Of Metallic Sheets At Various Temperatures - et. al., Dr BVS Rao, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
It is known that in warm and hot forming processes, the forming speed and with-it combined strain rate has immense role on material flow in bulk and sheet metal operations. In contrast, the influence of the strain rate on the flow curve has been rarely analysed at room temperature. This work analyses the influence of strain rate on flow curve of bimetallic sheets, Copper and Aluminium metals. Evaluation of the flow curve is carried out as a function of strain rate. In this work three different strain rates are considered for three different materials viz bimetallic sheets(Cu-Al), Copper and Aluminium. In addition to this ,the evaluation of flow curve at elevated temperatures is carried out. The Variation of mechanical properties with strain rate are plotted and analysed.